An Innovative Approach to Virtual Private Networks for Enhancing Digital Security and Accessibility - Ozdenizci Kose, Büşra; Coşkun, Vedat; Coskun, Arslan; Yaya, Senol (Institute of Electrical and Electronics Engineers Inc., 2024)
In today’s digital landscape, Virtual Private Networks (VPNs) are critical tools that ensure secure and private online interactions. They are crucial for protecting both individuals and enterprises from cyber threats while facilitating access to geographically restricted content. This study aims to investigate the trcVPN system, which proposes an innovative approach to VPN functionality designed to meet the complex demands of today's digital environment. trcVPN addresses the limitations of traditional VPN technologies by introducing advanced features that enhance security, user experience, and adaptability. The system integrates cutting-edge encryption protocols and dynamic connectivity options to ensure robust digital security and improved accessibility, thereby supporting various cybersecurity needs. Additionally, the designed trcVPNPrice module, a key innovation within the system, leverages geographic pricing differentials to offer users significant cost savings on a variety of online services, from airline tickets to hotel bookings. This study details the architectural and functional advancements of trcVPN that collectively enhance both the security and economic efficiency of internet usage. This comprehensive analysis underscores the importance of evolving VPN solutions to adapt to the global, interconnected landscape, where user needs and security challenges continuously evolve. © 2024 Elsevier B.V., All rights reserved.
6th International Congress on Human-Computer Interaction, Optimization and Robotic Applications, HORA 2024 -- Istanbul -- 200165
Keywords: accessibility; data encryption; dynamic routing; network security; secure communication; Virtual private network; VPN